Asymmetric effects of tourism development and green innovation on economic growth and carbon emissions in top 10 GDP countries - Razzaq, Asif; Fatima, Tehreem; Murshed, Muntasir (Journal of environmental planning and management, 2023)
This study aims to evaluate the impacts of international tourism development and green technology innovation on economic growth and carbon dioxide emissions in the top 10 GDP countries between 1995 and 2018. Our preliminary findings reject the preposition of data normality, which instigate us to apply a novel method of moments quantile regression. The overall results suggest that international tourism development facilitates economic growth and increases carbon dioxide emissions asymmetrically across the different levels of economic growth and carbon dioxide emissions. Specifically, the economic growth impacts are relatively large for the comparatively more developed nations while the adverse environmental impacts are relatively larger for the comparatively less-polluted nations; thus, the tourism led-economic growth hypothesis is verified. On the other hand, green technology innovation is found to facilitate economic growth and mitigate carbon dioxide emissions, especially in the context of the relatively more developed and polluted economies.